Measuring the Effect of Organizational Culture on Organizational Performance : A Case Study at B.M.Nagano Industries Sdn. Bhd. (Pasir Gudang, Johor) - Azie, Abd. Jalani (2004)
The purpose of this case study was to measure the effect of organizational culture on organizational performance. Demographic characteristics such as age, gender, place of origin, role, race, length of service and education qualification were also measured to examine the relation of organizational culture and organizational performance. Questionnaires contain of three sections which are demographic characteristics, organizational culture and organizational performance were used to collect data. In the demographic section, data gathered include age, gender, place of origin, marital status, education qualification, position, length of service and race. Denison Organizational Culture Questionnaire was used to measure organizational culture. Meanwhile for third section, organizational performance developed by Watskin and Marsick were used for the purpose of this study. The data were analyzed using SPSS 11.5. Five main hypotheses were tested using Oneway ANOVA and Pearson’s Correlation Coeeficient. From the result it was found that there are no positive relationship between organizational culture and organizational performance.